2002
DOI: 10.1103/physrevb.66.012501
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting anisotropy and evidence for intrinsic pinning in single crystallineMgB2

Abstract: We examine the superconducting anisotropy γc = (mc/m ab ) 1/2 of a metallic high-Tc superconductor MgB2 by measuring the magnetic torque of a single crystal. The anisotropy γc does not depend sensitively on the applied magnetic field at 10 K. We obtain the anisotropy parameter γc = 4.31 ± 0.14. The torque curve shows the sharp hysteresis peak when the field is applied parallel to the boron layers. This comes from the intrinsic pinning and is experimental evidence for the occurrence of superconductivity in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
(25 reference statements)
4
26
0
Order By: Relevance
“…(32) and (33), the ratio H || c2 /H ⊥ c2 is minimum at T c and increases as T decreases. This behavior has indeed been observed on many, mostly clean, M gB 2 samples 11,12,13,14,15,16,17,18,19,20,21 . By contrast, if impurities (like Al, Mg vacancies) cause the strongest intraband scattering in the "weak" π-band, (D 2 ≪ D 1 ), then the anisotropy parameter H || c2 /H ⊥ c2 would decrease as T decreases, The temperature dependence of H || c2 /H ⊥ c2 for these limiting cases is shown in Fig.…”
Section: B Temperature Dependence Of the Anisotropy Of Hc2mentioning
confidence: 79%
See 1 more Smart Citation
“…(32) and (33), the ratio H || c2 /H ⊥ c2 is minimum at T c and increases as T decreases. This behavior has indeed been observed on many, mostly clean, M gB 2 samples 11,12,13,14,15,16,17,18,19,20,21 . By contrast, if impurities (like Al, Mg vacancies) cause the strongest intraband scattering in the "weak" π-band, (D 2 ≪ D 1 ), then the anisotropy parameter H || c2 /H ⊥ c2 would decrease as T decreases, The temperature dependence of H || c2 /H ⊥ c2 for these limiting cases is shown in Fig.…”
Section: B Temperature Dependence Of the Anisotropy Of Hc2mentioning
confidence: 79%
“…So far all attempts to increase the critical temperature T c of M gB 2 by doping have been unsuccessful 9 . On the other hand, the significant potential of M gB 2 for applications 10 is limited by comparatively low upper critical fields H ⊥ c2 (0) ≃ 3 − 5T and H || c2 (0) ≃ 15 − 19T of hexagonal M gB 2 single crystals 11,12,13,14,15,16,17,18,19,20,21 , where the indices ⊥ and || correspond to the magnetic field H perpendicular and parallel to the ab plane, respectively. As far as H c2 is concerned, it can be increased by adding nonmagnetic impurities 22,23 , which are especially effective in the dirty limit, 2πk B T c < /τ , where τ is the elastic scattering time, is the Planck constant, and k B is the Boltzmann constant.…”
Section: Introductionmentioning
confidence: 99%
“…where R(α) = (cos 2 α + ǫ sin decreases from ≃ 2 − 3 to ≃ 1 as T decreases [46,47,48,49,50,51,52,53,54,55,56]. This behavior was explained by the two-gap theory in the clean limit [57,58,83,84].…”
Section: Anisotropy Of Hc1 and Hc2mentioning
confidence: 98%
“…Similarly, MgB 2 also has a layered structure, and it is described as a two-band superconductor with two gaps of Δσ and Δπ coming from boron p x,y orbitals and boron p z orbitals, respectively. Moreover, Takahashi et al [55] reported the exhibition of intrinsic pinning in single-crystalline MgB 2 by measuring the magnetic torque, and it originates from boron planes which act as the main superconducting layers in MgB 2 . The c-axis coherence length in MgB 2 is about 5 nm and even larger in the a-b plane.…”
Section: A-axis-oriented Mgb 2 Filmsmentioning
confidence: 99%
“…There are two J c peaks associated with H||ab and H||c, respectively. The peak at θ=0° can be understood as a result of the intrinsic pinning due to the layered structure of MgB 2 [55] or/and the interface pinning. The J c peak at θ=90° is believed to be originated in the grain boundaries of the columnar structure.…”
Section: Mgb 2 Columnar Thick Filmsmentioning
confidence: 99%